Lycopene supplementation does not change productive performance but lowers egg yolk cholesterol and gene expression of some cholesterol-related proteins in laying hens - Orhan, C.; Küçük, Ömer; Şahin, Nurhan.; Tuzcu, M.; Şahin, Kazım (Taylor & Francis Ltd, 2021)
1. This work examined the effects of purified lycopene (LYC) supplementation or a source of LYC as tomato powder (TP) on productive performance, egg yolk cholesterol levels as well as gene expression related to mechanism and regulation of cholesterol. 2. One hundred and fifty laying hens (Lohman LSL, hybrid) were randomly divided into one of three treatments, with 10 replicates of five hens per cage, totalling 50 hens per treatment. The hens were fed either a standard diet (control) or a standard diet supplemented with 20 mg purified lycopene/kg diet (LYC) or an equal amount of lycopene-containing tomato powder (TP) for 12 weeks. 3. Feed consumption, egg production, and feed efficiency remained similar among treatments (P >= 0.27). Supplementing lycopene, either as a purified form or in TP, increased the levels of serum and egg yolk lycopene and reduced serum and egg yolk cholesterol concentrations (P < 0.001). Supplementation in either form decreased gene expression for intestinal NPC1L1, MTP, ACAT2, hepatic SREBP1c, ACLY, and LXR alpha but increased hepatic ABCG5 and ABCG8 (P < 0.001). 4. The results of the present work revealed that egg yolk cholesterol metabolism is regulated by the modulation of a group of genes, particularly with LYC supplementation.
Keywords: Lycopene; tomato; egg yolk cholesterol; cholesterol metabolism; laying hens